2013
DOI: 10.1111/nph.12570
|View full text |Cite
|
Sign up to set email alerts
|

Rust fungi and global change

Abstract: Summary Rust fungi are important components of ecological communities and in ecosystem function. Their unique life strategies as biotrophic pathogens with complicated life cycles could make them vulnerable to global environmental change. While there are gaps in our knowledge, especially in natural plant–rust systems, this review of the exposure of rust fungi to global change parameters revealed that some host–rust relationships would decline under predicted environmental change scenarios, whereas others would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 129 publications
2
99
0
2
Order By: Relevance
“…Incidence and severity was also significantly (P<0.01) influenced by crop developmental stage and cropping history (previous crop planted). Similar findings were reported by Lin (2011) and Helfer (2014). There was no significant contribution by other disease observed in the field to rust incidence and severity, indicating that the presence of other diseases had not effect on the prevalence of rust disease.…”
Section: Rust Disease Incidence and Severitysupporting
confidence: 78%
See 2 more Smart Citations
“…Incidence and severity was also significantly (P<0.01) influenced by crop developmental stage and cropping history (previous crop planted). Similar findings were reported by Lin (2011) and Helfer (2014). There was no significant contribution by other disease observed in the field to rust incidence and severity, indicating that the presence of other diseases had not effect on the prevalence of rust disease.…”
Section: Rust Disease Incidence and Severitysupporting
confidence: 78%
“…The factors that contribute to the distribution and prevalence of the bean rust disease include altitude, ecological zones and human activities (Helfer, 2014;Lin, 2011). Helfer (2014) and Liebenberg and Pretorius (2010) reported that abiotic factors such as temperature, high humidity and leaf surface moisture; and biotic factor such as rust disease host range contribute to the epidemiology of rust disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific plant-pathogen interactions may be affected differently by high CO 2 , and any one interaction may be influenced by CO 2 levels in multiple ways. Increased CO 2 could influence plant disease resistance by altering the nutritional value of plant tissues, by modifying pathways involved in plant resistance, or by modulating pathogen vigor and virulence (Hibberd et al, 1996;Lake and Wade, 2009;Melloy et al, 2010Melloy et al, , 2014Helfer, 2014;Zhang et al, 2015). During longterm exposure to increases in CO 2 in an agronomic setting, secondary effects could result from changes in plant development or canopy density (Eastburn et al, 2010(Eastburn et al, , 2011.…”
mentioning
confidence: 99%
“…-The rust (Uredinales or Pucciniales) and smut (Ustilaginomycotina) fungi are obligate biotrophs and exclusively pathogenic on vascular plants, including lycophytes, ferns, gymnosperms, and most families of angiosperms (Begerow et al 2014, Helfer 2014. They are present in all modern terrestrial ecosystems containing plants.…”
Section: Comparison With Extant Fungimentioning
confidence: 99%